2022
DOI: 10.1021/acsanm.1c04569
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nanostructures for Molecular Sensing: A Review

Abstract: This review presents a comprehensive synopsis of the recent developments and achievements in the research of nanosensors composed of plasmonic nanoparticles (NPs) and silicon nanostructures (NSs) for effective trace-level molecular detection. This review focuses intensively on the methodologies for the preparation and enforcement of a variety of SiNSs including (a) metal nanoparticles decorated silicon nanowires (NWs), (b) metal nanodendrites (NDs) on Si substrate, (c) plasmonic NPs decorated nanocrystalline p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 363 publications
(511 reference statements)
0
18
0
1
Order By: Relevance
“…Surface-enhanced Raman spectroscopy/scattering (SERS) is one of the most fascinating analytic techniques for rapid, in-field, single-shot detection of analyte molecules finding impending applications in biomedicine, clinical, environmental detection, food safety, and so forth. ( Vendamani et al, 2022 ; Verma and Soni, 2022 ; Tzeng and Lin, 2020 ; Zhang et al., 2013 ; Powell et al., 2017 ; Ouyang et al., 2018 ; Xu et al., 2018 ; Zhu et al., 2021 ). This technique has also been favored in food inspection via examining antibiotic deposits in animal products ( Lirio et al., 2016 ; Li et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Surface-enhanced Raman spectroscopy/scattering (SERS) is one of the most fascinating analytic techniques for rapid, in-field, single-shot detection of analyte molecules finding impending applications in biomedicine, clinical, environmental detection, food safety, and so forth. ( Vendamani et al, 2022 ; Verma and Soni, 2022 ; Tzeng and Lin, 2020 ; Zhang et al., 2013 ; Powell et al., 2017 ; Ouyang et al., 2018 ; Xu et al., 2018 ; Zhu et al., 2021 ). This technique has also been favored in food inspection via examining antibiotic deposits in animal products ( Lirio et al., 2016 ; Li et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…32 The fluorescence emissions of undoped SiQDs and other types of SiQDs from the literature were commonly blue, thus they may be susceptible to interference from the fluorescence of biological samples when used as fluorescence markers. [1][2][3][4] Thus, the green fluorescence of the prepared N-SiQDs would be beneficial to the fluorescence imaging of the biological samples. 33 Additionally, the fluorescence intensity of the N-SiQDs was continuously monitored under UV irradiation for 1 h (Fig.…”
Section: Characterization Of the N-siqdsmentioning
confidence: 99%
“…As a class of emerging photoluminescent quantum dots, silicon quantum dots (SiQDs) were prominent for the large Stokes shift, adjustable fluorescent properties, and satisfactory chemical and photo stability. 1,2 Compared to bulk silica, SiQDs exhibit excellent photoluminescence as the size of the nanoparticles is reduced to less than the exciton Bohr radius (B4.2 nm) of silicon. [1][2][3][4] At this situation, the surface-related optical properties of the SiQDs significantly improve due to the increase of atom ratio on the surface and the enhancement of various quantum effects, such as the quantum size effect and quantum interference effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was shown that porous silicon could be used in the biodetection of miRNA on the basis of the surface plasmon resonance and surface-enhanced Raman spectroscopy (SERS) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%